Prediction of dry matter intake based on ruminal degradation from milking cows grazing coast-cross grass - Berchielli, T. T.; Soares, JPG; Aroeira, LJM; Furlan, C. L.; Salman, AKD; Da Silveira, R. N.; Malheiros, E. B. (Fundação Estudos Agrarios Luiz Queiroz (fealq), 2001)
Dry matter intake (DMI) of coast-cross grazing by crossbred Holstein-Zebu and Zebu lactating cows was calculated using in vitro dry matter digestibility from extrusa (four esophageal fistulated cows) and fecal output estimate with mordent chromium. Pasture was rotationally grazed with three days grazing period and 27 days testing period, adopting a stocking rate of 1.6 and 3.2 cows/ha, during the dry and rainy season respectively. Voluntary DMI was estimated from degradation characteristics using different equations. Predicted coast-cross DMI varied with models. The prediction of tropical forages dry matter intake from equations based in ruminal degradation parameters needs farther investigation before being employed in practice.
Keywords: degradability; dry matter intake; Grazing; lactating cows; prediction equations